Quem mora no livro didático: representações de gênero nos livros de matemática na virada do milênio - Casagrande, Lindamir Salete (2005)
This dissertation was developed with the objective of analyzing the gender representations in the Math school books for the fifth and sixth grades on the turn of the century. School books from the beginning of the decades 1990 and 2000 were analyzed. In order to make the research, I adopted the qualitative approach because I understood it was adequate to solve the problem-question. The research is one of the document type, while the school books constitute the empirical field. I searched to know how the genders are represented in this teaching tool because I understand the school books constitute an important support material for female teachers and male teachers, and mainly for female students and male students, as well as, in a “home” where the genders manifest in several situations. I also understand that the gender representations in the school books contribute to the building of the gender identities of children and teenagers. The data are divided into eleven categories defined with bases on the incidence of statements and illustrations that represent men and women in similar situations. The results were put in two chapters. The first one was destined to the gender representations in the public space. I could notice that such representations occur, most of the times, in dichotomyzed roles. The interaction between the genders is nor privileged, and neither their building by means of this interaction. The second chapter for showing the results was destined to the socialization of children through the family, playing and school situations. I noticed That there was interaction between the different genders, but teaching and taking care of the children is a feminine task. The representation of gender in the taking care of the family also occurs in dichotomyzed roles. The main difference observed in the gender representations in the school books in both periods (1990-1993 and 2000-2003) analyzed was the enhancing of the number of statements and illustrations with such representations on the second period, but with little difference in the form and in the situations in which men and women are represented. This fact shows that the school books have not incorporated the social transformations and, as a consequence, the changes in the gender relations that occurred on the turn of the century.